Integration of Islamic Values in Civic Education at Pesantren-Based Universities - Kurniasih, Maulana Dwi; Sastradiharja, EE Junaedi; Syaidah, Khasnah (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis article aims to examine the integration of Islamic values into civic education at pesantren-based higher education institutions. Using a qualitative research design, data were collected through in-depth interviews, participatory observations, and document analysis at Universitas Abdullah Faqih (UNKAFA) in Gresik, East Java. The study explores how Islamic teachings are integrated into the civic education curriculum and extracurricular activities to instill values such as patriotism, respect for the law, and political awareness. The findings demonstrate the effectiveness of this integrative model in producing graduates who are not only academically competent but also possess strong moral character and deep spirituality. Key findings include increased student engagement in social and civic responsibilities, the promotion of tolerance and respect for diversity, and the alignment of Islamic and national values. This approach offers a sustainable framework for character development and national identity formation while addressing challenges such as radicalism and social fragmentation. The implications of this research suggest that pesantren-based higher education institutions can serve as a model for harmonizing religious and civic education. Further research is recommended to quantitatively evaluate the impact of this model and explore its application in broader educational contexts.AbstrakArtikel ini bertujuan untuk mengkaji integrasi nilai-nilai Islam ke dalam pendidikan kewarganegaraan di institusi pendidikan tinggi berbasis pesantren. Dengan menggunakan desain penelitian kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen di Universitas Abdullah Faqih (UNKAFA) di Gresik, Jawa Timur. Penelitian ini mengeksplorasi bagaimana ajaran Islam diintegrasikan dalam kurikulum pendidikan kewarganegaraan dan kegiatan ekstrakurikuler, dengan tujuan menanamkan nilai-nilai seperti patriotisme, penghormatan terhadap hukum, dan kesadaran politik. Hasil penelitian menunjukkan efektivitas model integratif ini dalam menghasilkan lulusan yang tidak hanya kompeten secara akademik tetapi juga memiliki moral yang kuat dan spiritualitas yang mendalam. Temuan utama mencakup peningkatan keterlibatan mahasiswa dalam tanggung jawab sosial dan kewarganegaraan, promosi toleransi dan penghormatan terhadap keberagaman, serta keselarasan nilai-nilai Islam dan kebangsaan. Pendekatan ini menawarkan kerangka kerja yang berkelanjutan untuk pembangunan karakter dan pembentukan identitas nasional, sekaligus menjawab tantangan seperti radikalisme dan fragmentasi sosial. Implikasi penelitian ini menunjukkan bahwa institusi pendidikan tinggi berbasis pesantren dapat menjadi model harmonisasi pendidikan agama dan kewarganegaraan. Penelitian lanjutan direkomendasikan untuk mengevaluasi dampak model ini secara kuantitatif dan mengeksplorasi penerapannya dalam konteks pendidikan yang lebih luas. How to Cite: Kurniasih, M. D., Sastradiharja, EE. J., & Syaidah, K. (2024). Integration of Islamic Values in Civic Education at Pesantren-Based Universities. TARBIYA: Journal of Education in Muslim Society, 11(2), 179-196. doi:10.15408/tjems.v11i2.41447.